Proximal and distal outcomes of organizational socialization among new teachers: A mediation analysis - Tengku Ariffin, Tengku Faekah; Awang Hashim, Rosna; Yusof, Norhafezah (Taylor & Francis Group, 2014)
This study was designed to examine the relationship between socialization experience and the task performance of new teachers.It proposed to do this by testing a structural model.In explicating the relationship between the two constructs, teacher engagement in workplace learning activities and wellbeing were included in the structural model as plausible mediators.The study used a survey research method to gather data from a sample of 182 beginning teachers in northern peninsular Malaysia.Data were analyzed using SPSS version 16.0 and AMOS 16.0.The findings indicate that the structural model adequately fits the data. There is a significant indirect influence of socialization factors on the task performance of new teachers, with 81% of the variance explained.